Інформатизація освіти як вектор розвитку сучасного суспільства - Шаров, Сергій Володимирович; Шаров, Сергей Владимирович; Sharov, Sergii (My University, 2021)
UK: У статті розглядаються основні напрямки впровадження інформаційно-комунікаційних технологій в освітній процес. Зазначається, що розвиток інформаційного суспільства суттєво впливає на освітній процес. Розглядаються характерні ознаки інформаційного суспільства та інформатизації освіти. Звертається увага на перевагах електронних освітніх ресурсах, електронних засобах навчального призначення, електронних підручниках, дистанційної освіти та ін. EN: The article considers the main directions of implementation of information and communication technologies into the educational process. It is noted that the development of the information society significantly affects the educational process. There are considered the characteristic features of the informational society and informatization of education. Attention is paid to the advantages of electronic educational resources, electronic teaching aids, electronic textbooks, distance education, etc.
Informatization of Education as a Vector of Development of Modern Society
Keywords: інформаційне суспільство; інформатизації освіти; дистанційна освіта; електронні підручники; informational society; informatization of education; distance education; electronic textbooks